PENGARUH GOOD CORPORATE GOVERNANCE, STRUKTUR KEPEMILIKAN, DAN KARAKTERISTIK PERUSAHAAN TERHADAP NILAI PERUSAHAAN - NOVIA NOVIA; NELLIYANA NELLIYANA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to obtain empirical evidence about the effect of good corporate governance (audit committee, size of the commissioner’s board, and proportion of independent commissioner’s board), ownership structure and characteristics on the company's corporate value. These are managerial ownership, institutional ownership, leverage, profitability, firm size, audit committee, board size, and proportion of independent board of commissioners. This research uses 88 non-financial companies listed in Indonesia Stock Exchange selected using purposive sampling method during the period 2013 to 2016. The data of this research were analyzed using multiple linear regression analysis method. The results of this research indicated that the institutional ownership, proportion of independent board of commissioner, profitability, size of the board of commissioners, and firm size affect the value of the company. In the other hand managerial ownership, leverage, audit committee, and have no effect on company value.